Studi Fenomenologi Pengusaha Muda Penjual Ubi Kopong dalam Berwirausaha - Achmad Fachri; Yanladila Yeltas Putra (PRODUCTIVITY: Journal of Integrated Business, Management, and Accounting Research, 2025)
This research aims to understand the phenomenon experienced by sweet potato sellers in entrepreneurship. The approach used is qualitative with a phenomenological method. Data collection was carried out through unstructured interviews with a young entrepreneur selling sweet potatoes in Bukittinggi. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of this study reveal seven subthemes that describe the experience of potato sellers in running their businesses. This research highlights the important role of internalizing family values in building entrepreneurial interest, seller behavior in managing business, and their ability to face and overcome various obstacles, such as limited capital and market competition